Gerakan Anti Kapitalisme Global - Hiariej, Eric (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
Capitalism is contradiction. The flourish of liberal capitalism is met with a global scale of anti-capitalism, which ironically makes capitalism even stronger. Given the diversity of the the way in responding to capitalism embedded within globalization, this article reviews various ways of mapping anti capitalism movements, and assessing the implications of such diversity.